PENGARUH KEPEMIMPINAN TERHADAP KINERJA PEGAWAI DENGAN MOTIVASI SEBAGAI VARIABEL MEDIASI DI DINAS LINGKUNGAN HIDUP DAN KEBERSIHAN KABUPATEN BADUNG - Rizal Priyanto; Ni Luh Ketut Ayu Sudha Sucandrawati; Ni Made Yusmini (Nusantara Hasana Journal, 2023)
This research aims to analyze the influence of leadership on employee performance with motivation as a mediating variable at the Environment and Hygiene Service, Badung Regency. This research was structured descriptively using the PLS-SEM method using the SmartPLS 3.0 program. Where the object and population of this research are all employees of the Environment and Cleanliness Service of the North Kuta UPT unit, totaling 39 people. The sampling technique used is nonprobability sampling with purposive sampling technique. So the sample in this study amounted to 33 people. The data collection process involves interviews or direct observation of informants. The results of this research are the first. The results of the leadership variable test on employee performance have a positive and significant effect as seen from the results of the T-Statistics value of 2.409 which is greater than the critical value of 1.96. Second, the test results of the motivation variable on employee performance have a significant effect, seen from the T-Statistics value of 2.489, which is greater than the critical value of 1.96. Third, the test results of the motivation variable in the influence of leadership on employee performance are mediating, seen from the results of the T-Statistics value of 2.341, which is greater than the critical value of 1.96. The first conclusion from this research is that if leadership improves, employee performance will automatically increase as well. Second, motivation is an important factor in improving employee performance, that motivation can be caused by many factors such as working conditions and administration and organizational policies. These three studies show that motivation can mediate leadership on employee performance